Rapid volumetric gagCEST imaging of knee articular cartilage at 3 T: evaluation of improved dynamic range and an osteoarthritic population. (23rd May 2020) - Watkins, Lauren E.; Rubin, Elka B.; Mazzoli, Valentina; Uhlrich, Scott D.; Desai, Arjun D.; Black, Marianne; Ho, Gabe K.; Delp, Scott L.; Levenston, Marc E.; Beaupré, Gary S.; Gold, Garry E.; Kogan, Feliks
Abstract : Chemical exchange saturation transfer of glycosaminoglycans, gagCEST, is a quantitative MR technique that has potential for assessing cartilage proteoglycan content at field strengths of 7 T and higher. However, its utility at 3 T remains unclear. The objective of this work was to implement a rapid volumetric gagCEST sequence with higher gagCEST asymmetry at 3 T to evaluate its sensitivity to osteoarthritic changes in knee articular cartilage and in comparison with T 2 and T 1ρ measures. We hypothesize that gagCEST asymmetry at 3 T decreases with increasing severity of osteoarthritis (OA). Forty‐two human volunteers, including 10 healthy subjects and 32 subjects with medial OA, were included in the study. Knee Injury and Osteoarthritis Outcome Scores (KOOS) were assessed for all subjects, and Kellgren‐Lawrence grading was performed for OA volunteers. Healthy subjects were scanned consecutively at 3 T to assess the repeatability of the volumetric gagCEST sequence at 3 T. For healthy and OA subjects, gagCEST asymmetry and T 2 and T 1ρ relaxation times were calculated for the femoral articular cartilage to assess sensitivity to OA severity. Volumetric gagCEST imaging had higher gagCEST asymmetry than single‐slice acquisitions ( p = 0.015). The average scan‐rescan coefficient of variation was 6.8%. There were no significant differences in average gagCEST asymmetry between younger and older healthy controls ( p = 0.655) or between healthy controls and OA subjects ( p = 0.310). T 2 and T 1ρ relaxation times were elevated in OA subjects ( p < 0.001 for both) compared with healthy controls and both were moderately correlated with total KOOS scores (rho = −0.181 and rho = −0.332 respectively). The gagCEST technique developed here, with volumetric scan times under 10 min and high gagCEST asymmetry at 3 T, did not vary significantly between healthy subjects and those with mild‐moderate OA. This further supports a limited utility for gagCEST imaging at 3 T for assessment of early changes in cartilage composition in OA. Abstract : Volumetric gagCEST imaging at 3 T had higher gagCEST asymmetry than single‐slice acquisitions ( p = 0.015). The average scan‐rescan coefficient of variation was 6.8%. The gagCEST method presented here, with volumetric scan times under 10 min and high gagCEST asymmetry at 3 T, did not vary significantly between healthy subjects and those with mild‐moderate osteoarthritis ( p = 0.310).